Molecular mechanisms of acrolein-mediated myelin destruction in CNS trauma and disease. (July 2015) - Shi, R.; Page, J. C.; Tully, M.
Abstract: Myelin is a critical component of the nervous system facilitating efficient propagation of electrical signals and thus communication between the central and peripheral nervous systems and the organ systems that they innervate throughout the body. In instances of neurotrauma and neurodegenerative disease, injury to myelin is a prominent pathological feature responsible for conduction deficits, and leaves axons vulnerable to damage from noxious compounds. Although the pathological mechanisms underlying myelin loss have yet to be fully characterized, oxidative stress (OS) appears to play a prominent role. Specifically, acrolein, a neurotoxic aldehyde that is both a product and an instigator of OS, has been observed in studies to elicit demyelination through calcium-independent and -dependent mechanisms and also by affecting glutamate uptake and promoting excitotoxicity. Furthermore, pharmacological scavenging of acrolein has demonstrated a neuroprotective effect in animal disease models, by conserving myelin's structural integrity and alleviating functional deficits. This evidence indicates that acrolein may be a key culprit of myelin damage while acrolein scavenging could potentially be a promising therapeutic approach for patients suffering from nervous system trauma and disease.